Rodent models used in preclinical studies of deep brain stimulation to rescue memory deficits. (November 2021) - Faillot, Matthieu; Chaillet, Antoine; Palfi, Stéphane; Senova, Suhan
Highlights: DBS is a promising treatment for memory deficits of patients with TBI and stroke. Proof of concept studies in rodent models of TBI and stroke are needed. High heterogeneity is observed among models, which mirrors the clinical variability. We review the histological, behavioral and electrophysiological findings observed in each model. We propose a translational framework to assess the efficacy of DBS in rodent models. Abstract: Deep brain stimulation paradigms might be used to treat memory disorders in patients with stroke or traumatic brain injury. However, proof of concept studies in animal models are needed before clinical translation. We propose here a comprehensive review of rodent models for Traumatic Brain Injury and Stroke. We systematically review the histological, behavioral and electrophysiological features of each model and identify those that are the most relevant for translational research.